Hypothetical Learning Trajectory Bangun Ruang Sisi Datar Berbantuan Adobe Animate: Konteks Makanan Tradisional Jawa Tengah - Fanny Fakhrezi; Farida Nursyahidah; Irkham Ulil Albab (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2023)
Abstract:Some students have difficulty understanding the concept of building a flat side room resulting in a decrease in interest in learning mathematics. This study aims to produce a student learning trajectory in understanding the material of building a flat side room using the context of traditional Central Javanese food assisted by Adobe animate. This research is a design research that refers to the stages proposed by Susan McKenney. Data was collected through video recordings of learning activities, observations, interviews, and written data. The HLT design of the flat side space building material contains 5 characteristics of PMRI as developed by Arthur Bakker. The results showed that 5 student activities are expected to motivate and inspire teachers in carrying out learning to provide understanding of concepts to students, especially about building flat side spaces.Abstrak:Beberapa siswa mengalami kesulitan dalam memahami konsep bangun ruang sisi datar sehingga terjadi penurunan minat belajar matematika. Penelitian ini bertujuan menghasilkan lintasan belajar siswa dalam memahami materi bangun ruang sisi datar menggunakan konteks makanan tradisional Jawa Tengah berbantuan adobe animate. Penelitian ini merupakan design research yang mengacu kepada tahapan yang dikemukakan oleh Susan McKenney. Data dikumpulkan melalui rekaman video kegiatan pembelajaran, observasi, wawancara, dan data tertulis. Rancangan HLT materi bangun ruang sisi datar memuat 5 karakteristik PMRI seperti yang dikembangkan oleh Arthur Bakker. Hasil penelitian menunjukkan ada 5 aktivitas siswa yang diharapkan dapat memotivasi dan menjadi inspirasi bagi guru dalam melaksanakan pembelajaran agar memberikan pemahaman konsep kepada siswa khususnya tentang bangun ruang sisi datar.